SIMULTANEOUS QUANTIFICATION OF ACETYLSALICYLIC ACID AND CAFFEINE IN TABLETS BY FIRST-ORDER DERIVATIVE SPECTROSCOPY - MEDINA-LOPEZ, JOSE RAUL; GONZALEZ-SALAZAR, OMAR ALEJANDRO; CONTRERAS-JIMENEZ, JUAN MANUEL (International Journal of Applied Pharmaceutics, 2022)
Objective: To develop an apply a new and easy UV-derivative method for the simultaneous quantification of acetylsalicylic acid (ASA) and caffeine (CAF) in commercial tablets. Derivative spectroscopy is an analytical methodology used to identify drugs in a mixture of two or more compounds without use of toxic dissolvents that are involved in chromatographic determinations. Methods: Standard solutions of ASA (40-120 µg/ml) and CAF (5-25 µg/ml) were prepared with 0.1 M phosphate buffer pH 7.4. The zero-order spectra were determined from 200-300 nm. The method was validated according to International Conference on Harmonization (ICH) guidelines. An USP Apparatus 2 at 75 rpm with 900 ml of 0.1 M phosphate buffer pH 7.4 was used. For each drug, common dissolution data as the amount of drug released at 60 min (Q60), mean dissolution time (MDT), dissolution efficiency (DE), t50% and t85% were calculated. Results: ASA was identified at 245 nm and CAF at 295 nm in the first-derivative mode. The method was linear (R2>0.99, *P<0.05). The precision and accuracy of the method were within acceptable limits. Q60, MDT, DE, t50%, and t85% values for ASA were 102.09%, 8.18 min, 88.15%, 2.91 min, and 11.98 min, respectively. Same parameters for CAF were 99.17%, 5.21 min, 90.54%, 1.09 min, and 5.70 min, respectively. Conclusion: The proposed UV-derivative method is rapid and simple and can be easily adopted to determine the in vitro release curves of ASA and CAF from commercial tablets. The method generates reliable information that can be compared with published data.